Preparation and Properties of Agricultural Residuals-Iron Concentrate Pellets - Zhulin Liu; Xuegong Bi; Zeping Gao; Yayu Wang (Advances in Materials Science and Engineering)
In this paper, carbon-containing pellets were prepared by using crop-derived charcoal made from agricultural residuals and iron ore concentrates, and their pelletizing performance and properties were studied. Experimental results showed that the strengths of pellets were related to the particle size of concentrates and the content of moisture, bentonite, and crop-derived charcoal fines in the pelletizing mixture and the temperature of roasting and reduction. That the granularity of raw materials was fine and the bentonite content increased was beneficial to the improvement of pellet strengths. The suitable molar ratio of carbon to oxygen was 1.0 and the proper proportioning ratios of moisture and binder were 8.0% and 6.5%, respectively. The pellet strengths increased accordingly with increasing the reduction temperature, and when the temperature reached 1200°C, accompanied by the fast reduction of iron and the formation of crystal stock, the dropping strength of product pellets was 15 times and the compressive strength was 1650 N; this may be improved by grinding of the concentrate, leading to acceptable strength for the blast furnace.